2017
DOI: 10.14236/ewic/hci2017.89
|View full text |Cite
|
Sign up to set email alerts
|

Heuristics for Evaluating Multi-Touch Gestures in Mobile Applications

Abstract: Multi-touch gesture interaction is one of the main features that differentiate the current smart mobile era from the desktop-computing era. Heuristic evaluation is a popular usability evaluation method, mainly due to being less time-consuming, more cost effective, and applicable to different stages of the design and development phases. Researchers have provided their own sets of heuristics targeting domain specific mobile applications or some specific features (e.g., contextual behaviour). In this work, we spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The results obtained during the systematic literature review allowed the present work to identify some studies, such as the primary studies cited in the answer to the first question of research (RQ.1) of the SLR (Billiet al [52], Inostroza et al [14], Neto and Pimentel [48], Silva et al [28], Inostroza et al [49], Ajibola and Goosen [53] and Humayoun et al [50]), which propose heuristics focused on the context of mobile applications, evidencing that there is little research related in the area and also that there is a gap, allowing space for new contributions.…”
Section: ) Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results obtained during the systematic literature review allowed the present work to identify some studies, such as the primary studies cited in the answer to the first question of research (RQ.1) of the SLR (Billiet al [52], Inostroza et al [14], Neto and Pimentel [48], Silva et al [28], Inostroza et al [49], Ajibola and Goosen [53] and Humayoun et al [50]), which propose heuristics focused on the context of mobile applications, evidencing that there is little research related in the area and also that there is a gap, allowing space for new contributions.…”
Section: ) Discussionmentioning
confidence: 99%
“…Humayoun et al [50] propose a set of 15 heuristics focused on mobile applications that use multi-touch gestures (sixth line of Table 2). Based on the heuristic evaluation conducted by the authors, they concluded that through the proposed set of heuristics, the evaluators were able to find more usability problems than other heuristic proposals also focused on mobile applications, such as the paper of Joyce and Lilley [51], which also proposes a set of heuristics focused on the mobile context.…”
Section: ) Rq1 -Which Heuristics Are Used In the Context Of Mobile Applications To Evaluate The Quality Of The Product?mentioning
confidence: 99%
See 3 more Smart Citations